Ductile behaviour of optimised ferrocement corrugated flexural elements - Sheela, S.; Ganesan, N. (Journal of Structural Engineering, 2024)
Ferrocement is a highly versatile reinforced composite material suitable for several applications such as roofing and flooring elements, elements like doors, windows and lintels etc. in the building industry. Ferrocement elements can be made structurally more effective by reducing the deflection there by minimizing the cost of construction of members. This could be achieved by using the optimum cross section. An attempt was made to obtain an optimum cross section of the polymer modified corrugated ferrocement element by an efficient optimization technique like Genetic Algorithm (GA)¹. This Paper deals with the ductile behavior of polymer modified optimised ferrocement corrugated flexural elements. The study reveals that the engineering properties such as energy absorption capacity, ductility and cracking characteristics of corrugated element can be enhanced with the increase of polymer content and volume fraction of reinforcement.